Freedom of religious expression in Malaysia - Mohd Sani, Mohd Azizuddin (UUM Press, 2011)
There are always debates on the freedom of expression in today’s modern world more so in response to issues like freedom of religion, religious expression, hate speech, inter-faith dialogues etc. In Malaysia, issues especially those concerning race and religion are considered sensitive and therefore pose as obstacles to the implementation of complete religious freedom.Great care is taken not to impinge on the religious sensitivities of the various groups.It is understood that no one including the media can carry articles that question the faith or ridicule the religion and culture of the people in the country.Given that Islam is the religion of the Federation, great care is taken not to publish articles that cast slur, intended or otherwise, on the religion or its adherents.All media, including those operated by the opposition, follow this policy.Thus, religious expression has always been monitored by the government in order to protect the racial harmony in the multiracial, multicultural and multi-religious society of Malaysia.And this protection is provided for in the Constitution.This paper looks into some important issues that has caused some concern recently such as the position of Islam and freedom of religion, use of religion in politics, religious expression in the media, use of the word Allah by Christians, the publication of the Bible in the Malay language and the controversy over the so called attempt by an opposition party to make Christianity the official religion of Malaysia.The paper explains how these issues have been tackled by the government and society.